LEVERAGE EFFICIENCY IN THE CONTEXT OF DIGITAL PLATFORMS - Hanovskyi , Vasyl (Collection of scientific papers «ΛΌГOΣ», 2023)
Due to the historical development of the leverage doctrine, the term "leverage" has negative connotations and is often associated with actions that have no effect or purpose except to suppress competition. According to the general theory, leverage occurs when a firm uses its monopoly power in one market to extend it to an adjacent market, while using market power on this market by raising prices or limiting output or quality [1]. In antitrust circles, leverage has become a term that can be distinguished from behaviour that suppresses competition in an already dominant market [2]. Thus, by definition, leverage implies "the creation of a new or second monopoly" [3].